The use of apology strategies and gender differences among Iranian EFL postgraduate students in an ESL context - Abdolmalaki, Shahrbanou Ghorban; Abdul Ghani, Che An (Universiti Putra Malaysia Press, 2016)
Apology is defined as remedial exchange to produce social harmony after an offended action has been committed (Goffman, 1971). Apology is a type of speech act which has been the object of numerous studies (Demeter, 2006). The notion of apology may differ from one culture to another based on the social norms of the target culture. With this concern in mind, this study aims to identify apology strategies used by Iranian postgraduate students who are living in Malaysia. To this aim, 50 Iranian postgraduate students in one of the public universities in Malaysia (Universiti Putra Malaysia) were selected. In order to investigate the apology strategies, the questionnaire proposed by Sugimoto’s (1997) was used. The questionnaire was designed to compare the apology strategies used by male and female students. In this study, duration of stay and gender are the two variations which are also taken into consideration. The design of this study is quantitative and the framework to analyze the data from all responses was categorized according to Sugimoto’s model of apology speech acts model. The findings of this study revealed that male and female respondents differed in the use of strategies they used and also showed that the duration of stay would affect the use of apology that one can use in an apology situation. This study shows whether English learning experience in the EFL context of the participants’ home country helps them to use English in an ESL context communicatively.